G416(P) Response to resuscitation and outcome of infants with congenital diaphragmatic hernia. (27th April 2016) - O'Rourke, A; Ali, K; Bhat, P; Murthy, V; Milner, A; Greenough, A
Abstract : Aims: Approximately 1 in 3000 live births have a congenital diaphragmatic hernia (CDH). Affected infants have a high mortality and morbidity. The aim of this study was to determine whether the response to resuscitation differed between CDH infants who did and did not survive. Methods: Infants born at 34 weeks of gestation or greater and diagnosed antenatally with a CDH were eligible for entry into this study. All underwent our standard resuscitation protocol for CDH infants. None of the infants were subjected to face mask resuscitation. The infants were intubated as soon as possible after birth.. A neuromuscular blocking agent was given as soon as access was established and as soon as possible after intubation. The response to resuscitation was recorded using a respiratory function monitor which began as soon as the infants were intubated. Flow, airway pressure, tidal volume (VTe), compliance and end tidal carbon dioxide (ETCO2 ) were simultaneously recorded using the respiratory monitor. Oxygen saturation was also continuously recorded. Results: Thirty seven CDH infants were included in the study. Eleven infants died, their median gestational age and birthweight did not significantly differ from those who survived. During the first minute of recorded resuscitation, the peak inflation pressure (PIP) did not differ significantly between non survivors and survivors, but the VTe (median 1.89 vs. 2.81 ml/kg) (p = 0.010), the ETCO2 (median 11.7 vs. 42.2 mm Hg) (p = 0.025) and the compliance (0.06 vs. 0.09 ml/cmH2 O/kg) (p = 0.02) were significantly lower in the non survivors. In the last minute of resuscitation, the PIP was higher (32.5 vs. 30.3 cm H2 O) (p = 0.03), the VTe (3.23 vs. 4.66 ml/kg) (p = 0.004) and the compliance (0.10 vs. 0.16 ml/cmH2 O/kg) (p = 0.004) were lower in the non survivors. The maximum oxygen saturation (93 vs. 100%) achieved in the labour suite was lower in the non survivors (p = 0.044). Conclusion: Infants with CDH who did not survive responded less well even to initial resuscitation, as indicated by lower tidal volumes and ETCO2 levels despite similar inflation pressures.